Advances in quantum chemistry. - Lowdin, Per-Olov, 1916-2000 (Advances in quantum chemistry ;, 1991)
This volume presents a survey of the current developments in quantum chemistry. Topics covered include molecular orbital theory, the Feynman path integral formalism, the coupled cluster based polarization propagator method, and bounds to atomic and molecular energy functionals.